-11-4t=6+3(11-3t)

Simple and best practice solution for -11-4t=6+3(11-3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11-4t=6+3(11-3t) equation:


Simplifying
-11 + -4t = 6 + 3(11 + -3t)
-11 + -4t = 6 + (11 * 3 + -3t * 3)
-11 + -4t = 6 + (33 + -9t)

Combine like terms: 6 + 33 = 39
-11 + -4t = 39 + -9t

Solving
-11 + -4t = 39 + -9t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '9t' to each side of the equation.
-11 + -4t + 9t = 39 + -9t + 9t

Combine like terms: -4t + 9t = 5t
-11 + 5t = 39 + -9t + 9t

Combine like terms: -9t + 9t = 0
-11 + 5t = 39 + 0
-11 + 5t = 39

Add '11' to each side of the equation.
-11 + 11 + 5t = 39 + 11

Combine like terms: -11 + 11 = 0
0 + 5t = 39 + 11
5t = 39 + 11

Combine like terms: 39 + 11 = 50
5t = 50

Divide each side by '5'.
t = 10

Simplifying
t = 10

See similar equations:

| 2x^2-5+167=0 | | -(1+7v)-7b=111 | | 14x+22=7x-1 | | x(x-4)=x+5x+8 | | 10h-7=9h-26 | | X=96+7x | | 42=6-2/3x | | 7/10d-21/10 | | 4x-70=12y+2 | | 4p^2-2-p=2-p | | 5x-7x=7 | | -3-12-5+2/3= | | m^4/2m^4 | | 2x/3-5=x-1 | | b/5+1/6=13 | | .25x-2.5=1x+1 | | 6k-1k=5k+10 | | 133=-3(7n+4)-2 | | 10d+9=-7+2(4d+3) | | 5x-2x+4=10 | | 1000(9x-10)=50(656+100x) | | 2(x-7)+x=3(x-6)+4 | | y-60=7x-35 | | (w-6)=3(w+1) | | -12/-4+12/6+3= | | 4x-5x=-4 | | 4x^2+2=402 | | 4y-(-10)=26 | | -6b+8=-8-2(4b+1) | | 5(1-2x)+5=80 | | 7x+-1=2x+5 | | -2x(7-y)+4=-4 |

Equations solver categories